Kekuasaan dalam Perspektif Politik Islam - Sya’ban H. Muhammad (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2008)
Power in the perspective of Islamic politics is a trust that must be executed honestly and responsibly, both to Allah as the caretaker of the universe and to the people at large. When this understanding becomes ingrained in the beliefs and practices of the nation and state, the level of deviation and abuse of authority or power can be minimized. This article presents sovereignty and power based on Islam by examining the political constellation during the time of Prophet Muhammad.